Association of thyroid peroxidase antibodies with the rate of first-trimester miscarriage in euthyroid women with unexplained recurrent spontaneous abortion - Liu, Meilan; Wang, Dongyan; Zhu, Liqiong; Yin, Jianlan; Ji, Xiaohui; Zhong, Yilei; Gao, Yuan; Zhang, Jianping; Liu, Yukun; Zhang, Rui; Chen, Hui (Frontiers in Endocrinology, 2022)
Background Unexplained recurrent spontaneous abortion is a serious reproductive problem of unknown etiology. Thyroid peroxidase antibodies (TPO-Ab) may be associated with pregnancy outcomes in unexplained recurrent spontaneous abortion with normal thyroid function. Objective This study aimed to investigate the relationship between TPO-Ab and the first trimester miscarriage rate/live birth rate in women of unexplained recurrent spontaneous abortion with normal thyroid function. Methods We retrospectively analyzed the clinical data of 297 women who met our strict inclusion criteria, comparing the first trimester miscarriage rate/live birth rate between the TPO-Ab positive and TPO-Ab negative groups. For the same purpose, we also performed subgroup analysis. Results Of the included women, 76 (25.6%) were TPO-Ab positive, and 221 (74.4%) were negative. First trimester miscarriage rate differed between the two groups (36.8% vs 24.0%, RR = 1.54, 95% CI: 1.05–2.24, P = 0.030). In the younger subgroup (<35 years) and the primary RSA subgroup, First trimester miscarriage rate was also higher in the TPO-Ab positive group (33.3% vs 19.0%, RR = 1.75, 95% CI: 1.07–2.87, P = 0.030; 36.5% vs 21.7%, RR = 1.69, 95% CI: 1.10–2.58, P = 0.020). While the live birth rate was lower in women with TPO-Ab positive, the difference did not reach statistical significance, even in the subgroup analysis. Conclusion Our results suggest that TPO-Ab is associated with first trimester miscarriage rate in euthyroid women with unexplained recurrent spontaneous abortion.